Sosialisasi Membangun Rasa Percaya Diri Pada Anak SMAN 1 Polokarto - Natasya Odelia; Ardea Sri Pramesti; Ananda Novi Sila Alirga; Annisa Dian Karisma (Fakultas Teknik Universitas Maritim AMNI Semarang, 2023)
Everyone has different self-confidence. Confidence will grow by itself accompanied by encouragement in individuals who are trying to learn. But in reality, many children are born with a lack of self-confidence, so this hinders children from developing, as we often encounter cases of lack of self-confidence in adolescents, namely related to achievement, public speaking, body shape, family, friends or partners and much more. . Confidence is an individual's ability to develop oneself in a positive direction that is useful for oneself and the environment around them. The method used in this socialization is lecture. In this socialization, the subjects were teenagers at SMAN 1 Polokarto. This socialization aims to teach teenagers how to build self-confidence in themselves.